P-464 RESEARCHER MENTAL HEALTH OBSERVATORY (REMO) RECOMMENDATIONS TOWARDS IMPROVEMENT OF RESEARCHER MENTAL HEALTH AND WELL-BEING IN R.N. MACEDONIA - Mijakoski, Dragan; Stoleski, Sasho; Minov, Jordan; Jankoski, Darko (Oxford University Press (OUP), 2024)
Introduction: Relevant stakeholders, including ICOH, ILO, WHO, as well as EC put in their agenda labor protection, workplace safety culture, and mental health of workers. Researcher Mental Health and Well-being Manifesto strongly focuses on protection and improvement of mental health in researchers. The aim of this presentation is to discuss the opportunities for promotion of mental health within the academic community in R.N. Macedonia through application of recommendations proposed by Researcher Mental Health Observatory (ReMO) COST Action. Methods: We performed a desk analysis using relevant online resources as well as official and personal contacts to evaluate the national context in R.N. Macedonia concerning workplace mental health in researchers. ReMO key guidelines are used to develop actions to improve researcher mental health in R.N. Macedonia. Results: Despite raised awareness in recent years about workplace mental health and well-being, however the knowledge, attitudes, and practices about researcher mental health in R.N. Macedonia is still on a basic level. There is only occasional interest about this issue in policy makers, employers, workers, trade unions, and media. Specific actions with measurable outcomes have to be developed at community, institutional, and policy level. Open dialogue between stakeholders could be beneficial in systematic improvement of mental health of researchers. Strengthening of the Committee for Safety and Health at University level could help in the promotion of occupational safety and health in academia. Conclusion: Occupational health and safety strategy at national level should include mental health and well-being of researchers as an emerging issue.